High dielectric composite material and preparation method thereof
Through the method of low temperature grinding and thermal pressure treatment, high -agent composite materials with low cost of ceramic fillers and high dielectric constants are prepared, which solves the problem of increasing density, poor processing, and high cost caused by large fillers in the existing technology. It realizes the significant improvement of the dielectric constant and simplification of the process.
Patent Information
- Application Number
- CN202411590359.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-08
AI Technical Summary
The existing methods for preparing high-dielectric constant composite materials require a large amount of ceramic filler, resulting in increased density of composite materials, worsening processability and higher cost.
By mixing the dielectric ceramic powder and polymer particles at a temperature of -200 ℃ ~ -100 ℃, the ceramic powder is covered or scattered between the polymer particles to form a premium, and then the heat pressure treatment is performed. High -agent composite material with isolation structure.
The amount of ceramic fillers is reduced, the dielectric constant is improved, and the process is simple, the cost is low, and the non -pollution is not polluting. The dielectric constant is up to 60%compared with the traditional method.
Smart Images

Figure CN119371692A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of composite materials, and specifically relates to a high dielectric composite material and a preparation method thereof. Background Art
[0002] The most common method for preparing high dielectric constant composite materials is to compound polymers with ceramic fillers or conductive fillers with high dielectric constants. The current method for preparing high dielectric constant composite materials is to mix functional fillers with polymer matrix by melt blending or solution blending. This direct mixing method makes the filler randomly distributed throughout the polymer matrix. In order to obtain a satisfactory dielectric constant, a large filling amount is usually required, which increases the density of the composite material, deteriorates the processability, and is more expensive. Summary of the invention
[0003] Purpose of the invention: The embodiments of the present application provide a high dielectric composite material with low ceramic filler dosage and high dielectric constant and a preparation method thereof.
[0004] Technical solution: The present invention provides a method for preparing a high dielectric composite material, comprising the following steps:
[0005] The dielectric ceramic powder and the polymer particles are mixed and ground at a temperature of -200°C to -100°C, so that the dielectric ceramic powder is coated on the surface of the polymer particles or dispersed between the polymer particles to obtain a premix;
[0006] The premix is subjected to heat pressing to obtain a high dielectric composite material with an isolation structure.
[0007] In some embodiments, the mass ratio of the dielectric ceramic powder to the polymer particles is 3-40:60-97.
[0008] In some embodiments, the particle size of the dielectric ceramic powder is a nm, and the particle size of the polymer particles is b μm, satisfying:
[0009] 1×10 -4 ≤a / (b×1000)≤0.2.
[0010] In some embodiments, the particle size a nm of the dielectric ceramic powder satisfies: 10 nm ≤ a ≤ 200 nm; and / or
[0011] The particle size of the polymer particles is b μm and satisfies: 1 μm≤b≤100 μm.
[0012] In some embodiments, the dielectric ceramic powder is selected from at least one of perovskite ceramics and oxide ceramics; or
[0013] The dielectric ceramic powder is selected from at least one of barium titanate, strontium titanate, barium strontium titanate, calcium titanate, calcium copper titanate, titanium dioxide, magnesium oxide, silicon oxide, and zirconium oxide.
[0014] In some embodiments, the polymer is selected from at least one of polyvinylidene fluoride and copolymers thereof, polyimide, polymethyl methacrylate, polycarbonate, polypropylene, polyethylene, polyvinyl chloride, polyvinyl alcohol, polystyrene, polyethylene terephthalate, polyhexamethylene adipamide, polycaprolactam, thermoplastic polyurethane, ethylene-vinyl acetate copolymer, maleic anhydride grafted styrene-butadiene-styrene block copolymer, maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer, and maleic anhydride grafted polyolefin elastomer; or
[0015] The number average molecular weight of the polymer is 10,000 to 1,000,000; or
[0016] The glass transition temperature of the polymer is -100 to 300°C; or
[0017] The melting temperature of the polymer is -100 to 300°C.
[0018] In some embodiments, before the step of mixing and grinding the dielectric ceramic powder and the polymer particles at a temperature of -200°C to -100°C, the method further comprises:
[0019] The polymer particles are surface treated to form polar groups on the surface of the polymer particles; wherein the polar groups are selected from at least one of carbonyl, carboxyl, hydroxyl and amino groups.
[0020] In some embodiments, the surface treatment is plasma treatment, the pressure of the plasma treatment is 10-20 Pa, the power of the plasma treatment is 5-15 W, and the time of the plasma treatment is 2-10 min; the gas used in the plasma treatment is at least one selected from Ar, N2, O2, NH3, CO, CO2, and SO2.
[0021] In some embodiments, in the hot pressing treatment, the treatment temperature is 100-305° C., the treatment time is 5-30 min, and the treatment pressure is 10-20 MPa.
[0022] In some embodiments, the present application also provides a high dielectric composite material, which is prepared by the preparation method and includes, by mass percentage: 3wt% to 40wt% of dielectric ceramic powder and 60wt% to 97wt% of polymer; wherein part of the dielectric ceramic powder is aggregated to separate the polymer and form an isolation structure.
[0023] Beneficial effects: Compared with the prior art, the preparation method of a high dielectric composite material of the present application comprises the following steps: mixing and grinding dielectric ceramic powder and polymer particles at a temperature of -200°C to -100°C, so that the dielectric ceramic powder is coated on the surface of the polymer particles or dispersed between the polymer particles to obtain a premix; hot pressing the premix to obtain a high dielectric composite material with an isolation structure. The present application obtains a polymer-based composite material with an isolation structure through the preparation steps of low-temperature grinding and mixing combined with hot pressing. The preparation method is simple in process, low in cost, and pollution-free. It is a promising method for making polymer-based high dielectric composite materials.
[0024] A high dielectric composite material of the present application includes, by mass percentage: 3wt% to 40wt% of dielectric ceramic powder and 60wt% to 97wt% of polymer; wherein, the dielectric ceramic powder is partially aggregated to separate the polymer and form an isolation structure. In the high dielectric composite material of the present application, the isolation structure allows the dielectric ceramic powder to be regularly and continuously enriched in the composite matrix, which can greatly improve the dielectric constant of the composite material. Under the same formula composition, the dielectric constant of the composite material prepared by this method is increased by up to 60% compared with the traditional melt blending method and solution blending method. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 PVDF particles with surface coated with nano-barium titanate provided in the embodiments of the present application;
[0027] Figure 2 for Figure 1 A partial enlarged schematic diagram of
[0028] Figure 3 This is the SEM image of the brittle section of the high dielectric composite isolation structure;
[0029] Figure 4 Schematic diagram of the structure of the isolation dielectric composite material. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0031] In the description of the present application, it should be understood that the terms "upper", "lower", "top", "bottom", "inside", "outside", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. In the description of the present application, "plurality" means two or more than two, and at least one means one, two or more than two, unless otherwise clearly and specifically defined.
[0032] The applicant has found that polymer-based composite materials with high dielectric constants can not only store more electrical energy, but also integrate the advantages of polymers such as light weight, flexibility, and easy processing. In passive devices, the application of high dielectric constant composite materials in capacitors has attracted great attention. In the field of microelectronics technology, high dielectric constant composite materials can enable decoupling capacitors to have higher capacitance values and shorter operating distances on the equipment they serve. In addition to the electronics industry, high dielectric constant composite materials are widely used in civil and military applications, including active vibration control, aerospace, underwater navigation and surveillance, biomedical imaging, and non-destructive testing. Therefore, high dielectric constant polymer-based composite materials are a very active research direction in the field of functional materials, and have become one of the key basic materials for the development of cutting-edge fields such as electronic information, electric power, biomedicine, aerospace and navigation.
[0033] The most common method for preparing high dielectric constant composite materials is to compound polymers with ceramic fillers or conductive fillers with high dielectric constants. The polymers involved include polyvinylidene fluoride (PVDF) and its copolymers, epoxy resin (ER), polycarbonate (PC), polyimide (PI), polypropylene (PP), polymethyl methacrylate (PMMA), etc. The high dielectric ceramic particles used mainly include barium titanate, strontium titanate, barium strontium titanate, calcium copper titanate, etc. The conductive fillers mainly include silver, carbon nanotubes, graphene, polypyrrole, etc.
[0034] The current method for preparing high dielectric constant composite materials is to mix functional fillers with polymer matrix by melt blending or solution blending. This direct mixing method makes the filler randomly distributed throughout the polymer matrix. In order to obtain a satisfactory dielectric constant, a large filling amount is usually required, which increases the density of the composite material, deteriorates the processability, and increases the cost. In order to improve this situation, by regulating the distribution of fillers in the polymer matrix, it is expected that the functional filler will still have excellent dielectric properties when the addition amount is less than the conventional blending addition amount. Functional fillers can be conductive fillers. Although the use of conductive fillers as dielectric fillers to prepare dielectric composite materials will significantly improve the dielectric constant of the composite material, it will often cause a significant increase in dielectric loss, resulting in severe heating during actual use.
[0035] Based on this, this embodiment provides a high dielectric composite material and a preparation method, using nano-scale dielectric ceramic powder and micron-scale polymer particles treated with low-temperature plasma as raw materials, grinding them in liquid nitrogen, so that the nano-dielectric ceramic powder is coated on the surface of the polymer particles, and then the evenly ground powder is directly hot-pressed to obtain a high dielectric composite material with an isolation structure. The dielectric constant of the composite material obtained by this method is significantly improved compared with the dielectric constant of the composite material obtained by the traditional melt blending method and the solution blending method. Under the same formula composition, the maximum improvement is 60%. This method is simple in process, low in cost, and pollution-free. It is a promising method for making polymer-based dielectric composite materials.
[0036] In some embodiments, a method for preparing a high dielectric composite material of the present application comprises the following steps:
[0037] The dielectric ceramic powder and the polymer particles are mixed and ground at a temperature of -200°C to -100°C, so that the dielectric ceramic powder is coated on the surface of the polymer particles or dispersed between the polymer particles to obtain a premix;
[0038] The premix is subjected to heat pressing to obtain a high dielectric composite material with an isolation structure.
[0039] It can be understood that the method of the present application mixes and grinds the dielectric ceramic powder and the polymer particles at a temperature of -200°C to -100°C. Grinding at this temperature can avoid the influence of the temperature increase caused by grinding on the polymer particles. Therefore, the dielectric ceramic powder and the polymer particles can be fully mixed after low-temperature grinding; after sufficient mixing, a polymer-based dielectric composite material with an isolation structure can be obtained by hot pressing. This structure allows the dielectric ceramic powder to be regularly and continuously enriched in the composite material matrix, which is beneficial to the adjustment of the polarization direction in the electric field, enhance the local electric field, and obtain a high dipole moment, thereby greatly improving the dielectric constant of the composite material.
[0040] Further, the temperature of the mixed grinding can be any one of -100°C, -110°C, -120°C, -130°C, -140°C, -150°C, -160°C, -170°C, -180°C, -190°C, and -200°C, or a range between any two values.
[0041] In some embodiments, the temperature generated by grinding may exceed the glass transition temperature or melting temperature of the polymer particles. In order to avoid melting or decomposition of the polymer particles, it is necessary to control the grinding environment temperature to be less than or equal to the glass transition temperature or melting temperature of the polymer particles.
[0042] In some embodiments, the mass ratio of dielectric ceramic powder to polymer particles is 3-40:60-97. For example, the mass ratio of dielectric ceramic powder to polymer particles can be any one of 5:95, 10:90, 15:85, 20:80, 25:75, 30:70, and 35:65. It can be seen that the amount of dielectric ceramic powder added is less than that of conventional melt blending or solution blending, but a dielectric constant balanced with it can be achieved.
[0043] In some embodiments, the particle size of the dielectric ceramic powder is a nm, and the particle size of the polymer particles is b μm, satisfying: 1×10 -4 ≤a / (b×1000)≤0.2.
[0044] It can be understood that when the above relationship range is met, the dielectric ceramic powder can be ensured to be nanometer-sized and the polymer particles can be micrometer-sized; at this time, when the two are ground and mixed, the nanometer-sized dielectric ceramic powder is more likely to be coated on the surface of the micrometer-sized polymer particles, thereby improving the mixing uniformity of the two, and the excess dielectric ceramic powder can also be dispersed between the polymer particles. Among them, the range of a / (b×1000) can be 1×10 -4 , 2×10 -4 , 5×10 -4 , 8×10 -4 , 1×10 -3 , 2×10 -3 , 5×10 -3 , 8×10 -3 , 0.01, 0.02, 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, 0.2, or any range between any two values. Further, if a / (b×1000) is less than 1×10 -4, it means that the size of the dielectric ceramic powder is too small compared to the polymer particles, and it is impossible to ensure that the dielectric ceramic powder is evenly coated on the polymer particles; if a / (b×1000) is greater than 0.2, it means that the size of the dielectric ceramic powder is not highly differentiated compared to the size of the polymer particles, and it is difficult to ensure that the dielectric ceramic powder is coated on the polymer particles.
[0045] In some embodiments, the particle size a nm of the dielectric ceramic powder satisfies: 10 nm ≤ a ≤ 200 nm. For example, the particle size a nm of the dielectric ceramic powder can be any one of 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, and 200 nm, or a range between any two values. It is understood that when the particle size of the dielectric ceramic powder is within the above range, it can be ensured to be within a reasonable range to achieve better coating, so as to improve the dielectric constant of the composite material.
[0046] In some embodiments, to obtain a suitable particle size, the preparation method of the dielectric ceramic powder includes but is not limited to a hydrothermal synthesis method, a sol-gel method, a precipitation method, a microemulsion method, a ball milling method, and the like.
[0047] In some embodiments, the particle size of the polymer particles is bμm, satisfying: 1μm≤b≤100μm. For example, the particle size bμm of the polymer particles can be any one of 1μm, 2μm, 5μm, 8μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm, 100μm, or a range between any two values. It can be understood that when the particle size of the polymer particles is within the above range, it can be more conducive to providing attachment points for the dielectric ceramic powder to ensure that an isolation structure is formed in the composite material to further enhance the local electric field and obtain a high dipole moment.
[0048] In some embodiments, to obtain a suitable particle size, the preparation method of the polymer particles includes but is not limited to pulverization, non-solvent method, steam-induced phase separation method, suspension polymerization method, etc.
[0049] In some embodiments, the dielectric ceramic powder is selected from at least one of perovskite ceramics and oxide ceramics.
[0050] In some embodiments, the dielectric ceramic powder is preferably at least one selected from barium titanate, strontium titanate, barium strontium titanate, calcium titanate, calcium copper titanate, titanium dioxide, magnesium oxide, silicon oxide, and zirconium oxide.
[0051] In some embodiments, the polymer is selected from at least one of polyvinylidene fluoride and its copolymers, polyimide, polymethyl methacrylate, polycarbonate, polypropylene, polyethylene, polyvinyl chloride, polyvinyl alcohol, polystyrene, polyethylene terephthalate, polyhexamethylene adipamide, polycaprolactam, thermoplastic polyurethane, ethylene-vinyl acetate copolymer, maleic anhydride grafted styrene-butadiene-styrene block copolymer, maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer, and maleic anhydride grafted polyolefin elastomer. Among them, the polyvinylidene fluoride copolymer is selected from at least one of poly(vinylidene fluoride-trifluoroethylene) (P(VDF-TrFE)), poly(vinylidene fluoride-tetrafluoroethylene) (P(VDF-TFE)), poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)), poly(vinylidene fluoride-chlorotrifluoroethylene) (P(VDF-CTFE)), poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) (P(VDF-TrFE-CFE)), poly(vinylidene fluoride-trifluoroethylene-chlorodifluoroethylene) (P(VDF-TrFE-CDFE)), poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene) (P(VDF-TrFE-CTFE)), and poly(vinylidene fluoride-trifluoroethylene-hexafluoropropylene) (P(VDF-TrFE-HFP)).
[0052] In some embodiments, the number average molecular weight of the polymer is 10,000 to 1,000,000. For example, it can be any one of 10,000, 20,000, 50,000, 80,000, 100,000, 200,000, 300,000, 400,000, 500,000, 600,000, 700,000, 800,000, 900,000, 1,000,000, or any range between two values. When the number average molecular weight of the polymer meets the above range, it can be ensured to have good melt viscosity and mechanical strength, ensuring the integrity of the isolation structure during hot pressing and the mechanical properties of the composite material.
[0053] In some embodiments, the glass transition temperature of the polymer is -100 to 300°C. For example, it can be any one of -100°C, -90°C, -80°C, -70°C, -60°C, -50°C, -40°C, -30°C, -20°C, -10°C, 0°C, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 150°C, 200°C, 250°C, 300°C, or a range between any two values. The glass transition temperature of a polymer refers to the temperature at which the polymer changes from a glassy state to a highly elastic state in which the polymer chain segments can move freely during the heating process. When the above range is met, on the one hand, it becomes brittle at low temperatures to make it easier to mix evenly with dielectric ceramic powder, and on the other hand, it can also broaden the use temperature range of the composite material.
[0054] In some embodiments, the melting temperature of the polymer is -100 to 300°C. For example, it can be any one of -100°C, -90°C, -80°C, -70°C, -60°C, -50°C, -40°C, -30°C, -20°C, -10°C, 0°C, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 150°C, 200°C, 250°C, 300°C, or a range between any two values. The melting temperature of a polymer refers to the temperature at which the polymer changes from a solid state to a liquid state during the heating process. When the above range is met, it can be ensured that the polymer particles will not melt due to the increase in temperature during the grinding and mixing process.
[0055] In some embodiments, before the step of mixing and grinding the dielectric ceramic powder and the polymer particles at a temperature of -200°C to -100°C, the method further comprises:
[0056] The polymer particles are surface treated to form polar groups on the surface of the polymer particles; wherein the polar groups are selected from at least one of carbonyl, carboxyl, hydroxyl and amino groups.
[0057] It is understandable that polar groups can ensure that dielectric ceramic powder is better coated on the surface of polymer particles. This is because the surface of dielectric ceramic powder usually has a certain polarity, such as the oxide surface with hydroxyl (-OH), etc. The introduction of polymer particles with polar groups can react with the surface of dielectric ceramic powder by polar interactions such as hydrogen bonding and electrostatic interaction, thereby increasing the adsorption and adhesion between the two. In addition, polar groups can also react chemically with the surface of dielectric ceramic powder to form chemical bonds or covalent bonds, thereby achieving a more solid powder coating. For example, carboxyl groups (-COOH) can react with metal ions on the surface of oxides by coordination bonds or esterification reactions. The introduction of polar groups can include: using surface modifiers with polar groups, such as carboxylic acids, amines, alcohols, etc., to introduce polar groups into the surface of polymer particles by solution treatment or physical adsorption; or introducing polar groups into the surface of polymer particles by chemical reaction; or introducing polar groups into the surface of polymer particles by surface treatment such as plasma, ozone treatment, etc.
[0058] In some embodiments, the surface treatment is plasma treatment, the pressure of the plasma treatment is 10-20 Pa, the power of the plasma treatment is 5-15 W, and the time of the plasma treatment is 2-10 min; the gas used in the plasma treatment is at least one selected from Ar, N2, O2, NH3, CO, CO2, and SO2. It is understandable that plasma treatment can be completed in a short time and is an efficient surface treatment method. Plasma treatment can achieve uniform treatment of the entire surface of the polymer particles, so that the introduced polar groups are evenly distributed. Plasma treatment can introduce different polar groups to the surfaces of different types of polymer particles by selecting different plasmas and treatment conditions, which makes plasma treatment more flexible and applicable.
[0059] In some embodiments, during the hot pressing treatment, the treatment temperature is 100-305° C., the treatment time is 5-30 min, and the treatment pressure is 10-20 MPa.
[0060] It can be understood that the hot pressing treatment includes a vacuum oven molding method or a flat plate vulcanizing machine molding method.
[0061] In some embodiments, the vacuum oven forming method comprises the following steps:
[0062] (1) Adjust the oven to a suitable temperature, which is the melting temperature of the polymer and depends on the specific polymer;
[0063] (2) placing the mold containing the uniform premix into an oven, evacuating the oven, and molding in a vacuum state for 30 minutes, then turning off the heating and cooling naturally to room temperature to obtain a high dielectric composite material with an isolation structure.
[0064] In some embodiments, the plate vulcanizing press molding method comprises the following steps:
[0065] (1) Place the mold containing the premix on a cold press vulcanizer, pressurize to 10-15 MPa, and maintain for 30 minutes;
[0066] (2) transferring the mold of step (1) to another hot press vulcanizer, the temperature of which should be set to the melting temperature of the polymer, pressurizing to 10-15 MPa, and maintaining for 10 min;
[0067] (3) The mold of step (2) is transferred to a cold press vulcanizer, pressurized to 10-15 MPa, and cooled for 10 minutes to obtain a high dielectric composite material with an isolation structure.
[0068] Among them, the temperature of the flat vulcanizer molding method is better controlled and the pressure is greater, so the preparation effect is better.
[0069] In some embodiments, the preparation method of the high dielectric composite material specifically includes: using nano-scale dielectric ceramic powder and micron-scale polymer particles treated with surface plasma as raw materials, grinding them in liquid nitrogen, so that the nano-ceramic powder is coated on the surface of the polymer particles or dispersed in the gaps between the polymer particles; directly hot pressing the evenly ground powder to obtain a high dielectric composite material with an isolation structure.
[0070] In some embodiments, the embodiments of the present application also provide a high dielectric composite material, which includes, by mass percentage: 3wt% to 40wt% of dielectric ceramic powder and 60wt% to 97wt% of polymer; wherein, part of the dielectric ceramic powder is aggregated to separate the polymer and form an isolation structure.
[0071] In some embodiments, preferably, the embodiments of the present application further provide a high dielectric composite material, which comprises, by mass percentage, 5wt% to 25wt% of dielectric ceramic powder and 75wt% to 95wt% of polymer.
[0072] In some embodiments, preferably, the embodiments of the present application further provide a high dielectric composite material, which comprises, by mass percentage, 10 wt % to 20 wt % of dielectric ceramic powder and 80 wt % to 90 wt % of a polymer.
[0073] In some embodiments, preferably, the embodiments of the present application further provide a high dielectric composite material, which comprises, by mass percentage, 10 wt % to 15 wt % of dielectric ceramic powder and 85 wt % to 90 wt % of a polymer.
[0074] In some embodiments, the present embodiment provides a polymer-based dielectric composite material with an isolation structure, which allows the dielectric ceramic powder to be regularly and continuously enriched in the composite matrix, which is conducive to adjusting the polarization direction in the electric field, enhancing the local electric field, and obtaining a high dipole moment. Under the same formula composition, the dielectric constant of the composite material prepared in this embodiment is increased by up to 60% compared with the traditional melt blending method and solution blending method.
[0075] Example 1
[0076] (1) Raw materials and formula
[0077] Raw materials: PVDF microspheres: First, dissolve PVDF resin in N,N-dimethylacetamide with a solid content of 20wt%, and stir magnetically at 70°C and 500rpm for 8h to obtain a PVDF homogeneous solution. Then pour the PVDF homogeneous solution into a clean petri dish and place it in an environment of 30°C and 100% humidity for 12h. After 12h, take out the sample, wash it with deionized water, filter it, and dry it at 60°C for 48h to obtain PVDF microspheres with a particle size of 2-3μm and a molecular weight of 50,000.
[0078] Nano-barium titanate: obtained by hydrothermal synthesis, with a particle size of 100nm.
[0079] Formula: The mass ratio of PVDF to barium titanate is 75:25.
[0080] (2) Filler coating on polymer surface
[0081] The PVDF microspheres were treated with low-temperature plasma under the following conditions: argon atmosphere, treatment power 100W, treatment pressure 10Pa, and treatment time 10min. The treated microspheres were mixed and ground with nano-barium titanate in liquid nitrogen (-196°C) to obtain a premix. Figure 1 and Figure 2 , it can be clearly seen that nano-barium titanate is coated on the surface of PVDF microspheres.
[0082] (3) Preparation of isolation structure
[0083] Place the mold with the uniform premix on a cold plate vulcanizer, pressurize to 10MPa, and keep it for 30 minutes. Then transfer the mold to another hot plate vulcanizer at 200℃, pressurize to 10MPa, and keep it for 15 minutes. Then transfer the mold to a cold plate vulcanizer, pressurize to 10MPa, and cool for 10 minutes. Figure 3 , a high dielectric composite material with an isolation structure is obtained by opening a mold.
[0084] See also Figure 4 , which is a schematic diagram of the structure of the isolated dielectric composite material. It can be seen from the figure that the dielectric ceramic powder is isolated by the polymer and is continuously distributed in the polymer to form a three-dimensional network structure.
[0085] Example 2
[0086] The specific preparation method is the same as that in Example 1, except that: the preparation raw materials in Example 2 are PVDF microspheres and barium titanate, and the mass ratio of the two is 80:20; and the particle size of the preparation raw materials is different from that in Example 1.
[0087] Example 3
[0088] The specific preparation method is the same as that in Example 1, except that the preparation raw materials in Example 3 are PVDF and strontium titanate, the mass ratio of the two is 90:10, and the particle size of the preparation raw materials is different from that in Example 1.
[0089] Example 4
[0090] The specific preparation method is the same as that in Example 1, except that the raw materials for preparation in Example 4 are polymethyl methacrylate (PMMA) and strontium titanate, the mass ratio of the two is 69:31, and the particle size of the raw materials for preparation is different from that in Example 1.
[0091] Example 5
[0092] The specific preparation method is the same as that in Example 1, except that the preparation raw materials in Example 5 are polyvinyl chloride (PVC) and barium titanate, the mass ratio of the two is 90:10, and the particle size of the preparation raw materials is different from that in Example 1.
[0093] Example 6
[0094] The specific preparation method is the same as that in Example 1, except that the preparation raw materials in Example 6 are polyvinyl chloride (PVC) and barium strontium titanate, the mass ratio of the two is 83:17, and the particle size of the preparation raw materials is different from that in Example 1.
[0095] Example 7
[0096] The specific preparation method is the same as that in Example 1, except that the raw materials for preparation in Example 7 are polystyrene (PS) and barium titanate, the mass ratio of the two is 68:32, and the particle size of the raw materials for preparation is different from that in Example 1, and the grinding temperature is different.
[0097] Example 8
[0098] The specific preparation method is the same as that in Example 1, except that the raw materials for preparation in Example 8 are PS and calcium copper titanate, the mass ratio of the two is 70:30, and the particle size of the raw materials for preparation is different from that in Example 1, and the grinding temperature is different.
[0099] Comparative Example 1
[0100] The raw materials used are the same as those in Example 1, except that the mass ratio of PVDF to barium titanate is 99:1.
[0101] Comparative Example 2
[0102] The raw materials used are the same as those in Example 1, except that the mass ratio of PVDF to barium titanate is 50:50.
[0103] Comparative Example 3
[0104] The raw materials used are the same as those in Example 1, except that the PVDF microspheres and nano-barium titanate are mixed and ground at room temperature (25° C.) to obtain a premix.
[0105] Comparative Examples 4-5
[0106] The raw materials used are the same as those in Example 1, except that the particle size a nm of the dielectric ceramic powder and the particle size b μm of the polymer particles do not satisfy 1×10 -4 The range is ≤a / (b×1000)≤0.2.
[0107] Comparative Example 6
[0108] The raw materials used are the same as those in Example 1, except that PVDF with a particle size of 2-3 μm and barium titanate with a particle size of 100 nm are directly mixed evenly on a double-roll mill at a mass ratio of 75:25 without grinding. The mixed PVDF / barium titanate composite material is placed in a mold and placed on a hot-pressing plate vulcanizer at 200°C, pressurized to 10 MPa, and maintained for 15 minutes. The mold is then transferred to a cold-pressing plate vulcanizer, pressurized to 10 MPa, cooled for 10 minutes, and opened to obtain a sample.
[0109] The raw materials, particle sizes and process parameters used in the above Examples 1-8 and Comparative Examples 1-6 are shown in Table 1. The characterization properties of the obtained high dielectric composite material are shown in Table 2.
[0110] Among them, the characterization performance includes dielectric constant and dielectric loss, and the dielectric constant and dielectric loss are obtained by a precision impedance analyzer.
[0111] Grinding temperature: -196℃ is processed in liquid nitrogen environment; other temperatures such as -130℃, -150℃, etc. can be processed in ultra-low temperature refrigerators or other low-temperature grinding equipment.
[0112] Table 1
[0113]
[0114]
[0115] Table 2
[0116]
[0117] In Table 2: * indicates that the sample cannot be hot-pressed, so there is no data for dielectric constant and dielectric loss.
[0118] It can be seen from Table 1 and Table 2 that the dielectric constant of the high dielectric composite material with an isolation structure is significantly improved compared to the polymer. In Comparative Example 1, the ceramic powder content is too low and the isolation structure cannot be formed; in Comparative Example 2, the ceramic powder content is too high, and a large amount of ceramic powder cannot be coated on the surface of the polymer microspheres. The stratification is obvious after premixing and cannot be hot-pressed; in Comparative Example 3, the ceramic powder cannot be effectively dispersed because it is not ground below the glass transition temperature of the polymer; the particle size of the ceramic powder in Comparative Examples 4 and 5 is too large or too small to be effectively coated on the surface of the polymer microspheres, making it difficult to form an isolation structure. In Comparative Example 6, the ceramic powder is directly melt-blended, and the ceramic powder is randomly dispersed, and no isolation structure is formed. Compared to the above-mentioned Comparative Examples 1-6, the high dielectric composite material prepared by Examples 1-8 with an isolation structure has a significantly improved dielectric constant.
[0119] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0120] The above is a detailed introduction to a high dielectric composite material and a preparation method thereof provided in the embodiments of the present application, and the principles and implementation methods of the present application are explained using specific examples. The description of the above embodiments is only used to help understand the technical solution and core idea of the present application; ordinary technicians in this field should understand that: they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some of the technical features therein with equivalents; and these modifications or replacements do not make the essence of the corresponding technical solution deviate from the scope of the technical solution of the embodiments of the present application.
Claims
1. A method for preparing a high dielectric composite material, characterized in that: The following steps are involved: The dielectric ceramic powder and the polymer particles are mixed and ground at a temperature of -200°C to -100°C, so that the dielectric ceramic powder is coated on the surface of the polymer particles or dispersed between the polymer particles to obtain a premix; The premix is subjected to heat pressing to obtain a high dielectric composite material with an isolation structure.
2. The method for preparing a high dielectric composite material according to claim 1, characterized in that: The mass ratio of the dielectric ceramic powder to the polymer particles is 3-40:60-97.
3. The method for preparing a high dielectric composite material according to claim 1, characterized in that: The particle size of the dielectric ceramic powder is a nm, and the particle size of the polymer particles is b μm, satisfying: 1×10 -4 ≤a / (b×1000)≤0.2。 4. The method for preparing a high dielectric composite material according to claim 3, characterized in that: The particle size a nm of the dielectric ceramic powder satisfies: 10 nm≤a≤200 nm; and / or The particle size of the polymer particles is b μm and satisfies: 1 μm≤b≤100 μm.
5. The method for preparing a high dielectric composite material according to claim 1, characterized in that: The dielectric ceramic powder is selected from at least one of perovskite ceramics and oxide ceramics; or The dielectric ceramic powder is selected from at least one of barium titanate, strontium titanate, barium strontium titanate, calcium titanate, calcium copper titanate, titanium dioxide, magnesium oxide, silicon oxide, and zirconium oxide.
6. The method for preparing a high dielectric composite material according to claim 1, characterized in that: The polymer is selected from at least one of polyvinylidene fluoride and copolymers thereof, polyimide, polymethyl methacrylate, polycarbonate, polypropylene, polyethylene, polyvinyl chloride, polyvinyl alcohol, polystyrene, polyethylene terephthalate, polyhexamethylene adipamide, polycaprolactam, thermoplastic polyurethane, ethylene-vinyl acetate copolymer, maleic anhydride grafted styrene-butadiene-styrene block copolymer, maleic anhydride grafted styrene-ethylene-butylene-styrene block copolymer, and maleic anhydride grafted polyolefin elastomer; or The number average molecular weight of the polymer is 10,000 to 1,000,000; or The glass transition temperature of the polymer is -100 to 300°C; or The melting temperature of the polymer is -100 to 300°C.
7. The method for preparing a high dielectric composite material according to claim 1, characterized in that: Before the step of mixing and grinding the dielectric ceramic powder and the polymer particles at a temperature of -200°C to -100°C, the method further comprises: The polymer particles are surface treated to form polar groups on the surface of the polymer particles; wherein the polar groups are selected from at least one of carbonyl, carboxyl, hydroxyl and amino groups.
8. The method for preparing a high dielectric composite material according to claim 7, characterized in that: The surface treatment is plasma treatment, the pressure of the plasma treatment is 10~20 Pa, the power of the plasma treatment is 5~15 W, and the time of the plasma treatment is 2~10 min; the gas used in the plasma treatment is at least one selected from Ar, N2, O2, NH3, CO, CO2, and SO2.
9. The method for preparing a high dielectric composite material according to claim 1, characterized in that: In the hot pressing treatment, the treatment temperature is 100-305°C, the treatment time is 5-30 min, and the treatment pressure is 10-20 MPa.
10. A high dielectric composite material, prepared by the preparation method according to any one of claims 1 to 9, characterized in that: In terms of mass percentage, the present invention comprises: 3wt% to 40wt% of dielectric ceramic powder and 60wt% to 97wt% of polymer; wherein part of the dielectric ceramic powder is aggregated to separate the polymer and form an isolation structure.
Citation Information
Patent Citations
Novel dielectric composite material
CN109627694A
Plastic low-dielectric-loss film as well as preparation method and application thereof
CN116515316A
Modified polyethylene composite material and preparation method thereof, and water-tree-resistant cross-linked polyethylene insulation material containing modified polyethylene composite material
CN117964923A
Ceramic-filled fluoropolymer composite containing polymeric powder for high frequency circuit substrates
US5922453A
Cited By
Polystyrene composite board as well as preparation method and application thereof
CN121378982A
Polystyrene composite board and preparation method and application thereof
CN121378982B